Does the Efficacy of Behavior Management Techniques Differ Between Children From Single-Child and Multi-Child Families?: A Quasi-Experimental Study - Lina Dai; Lina Dai; Lina Dai; Tingting Wu; Tingting Wu; Yun Hu; Yun Hu; Yun Hu; Shunyi Li; Shunyi Li; Shunyi Li; Weiwei Liu (Frontiers Media S.A., 2022)
AimBehavior management techniques (BMTs) efficiently deliver dental treatment to children with dental anxiety. The objective of this quasi-experimental study was to examine whether the efficacy of BMTs applied for the improvement of compliance in pediatric patients differs between children 3-10-year-olds from single-child and multi-child families.Materials and MethodsIn this quasi-experimental, 197 caregiver-child couples were divided into two groups: single-child group (116 couples) and multi-child group (81 couples). Children's pre- and post-treatment anxiety levels were measured by facial mood scale (FMS) and Frankl Behavior Rating Scale (FBRS), respectively.Caregivers' dental anxiety was measured by the Chinese version of the Modified Dental Anxiety Scale (MDAS), which was included in the self-designed questionnaire. Data were analyzed by using the Mann-Whitney U-test, chi-square tests, and binary multivariate regression analysis.ResultsThere was no statistically significant difference in the demographic characteristics of the children between the two groups. BMTs were found to be capable of reducing children's dental anxiety (CDA): the compliance rate was 45.69-88.79% in the single-child group and 44.44-85.79% in the multi-child group pre- and post-BMTs, but there was no significant difference in the change of compliance between the two groups (p > 0.05). In the subgroup analysis, parenting style (odds ratio [OR] = 0.054, p < 0.05) and father's education (OR = 8.19, p < 0.05) affected the varies of children's compliance in the single-child group. In contrast, in the multi-child group, gender (OR = 8.004, p < 0.05) and mother's occupation (OR = 0.017, p < 0.05) were associated with these changes in compliance.ConclusionsIn this study, BMTs were proved to be beneficial in improving compliance in 3- to 10-year-olds children in dental treatment. Though there was no significant difference in the change of compliance between children from single-child and multi-child families, different associated factors may affect the two groups. Therefore, the related family factors should be taken into account when professionals manage each child's behavior in dental practice.